Caffeine in doping control: Determination of 13C in urinary excreted caffeine - Flenker, U.; Schänzer, W. (European Journal of Sport Science, 2001)
The ratio of the 2 stable carbon isotopes 13C and 12C reveals synthetic or natural origin of caffeine. 13C was measured in caffeine isolated from several beverages, several pharmaceutical preparations, and in caffeine obtained from urine samples collected during routine doping controls. Caffeine in soft drinks, "energy drinks," and pharmaceutical products showed 13C depletion typical for synthetic material. Urinary caffeine mostly showed values typical for tea or coffee products. One urine sample testing positive for caffeine showed evidence for synthetic material. This sample contained 25 mg/ml caffeine, whereas a threshold level of 12 mg/ml has been established by sports federations.